MODERN THEORY OF STATE AND LAW AS METHODOLOGICAL LEGAL THE SCIENCE (Western European Journal of Historical Events and Social Science, 2024)
The relevance of this scientific article is justified by the ambiguous assessment of the modern general theory of state in the system of legal sciences, attempts at both the theoretical and practical levels to downgrade its high status.